THE ROLE OF SOVEREIGN DEBTS IN THE DEVELOPMENT OF THE ACTUAL MACROECONOMIC ENVIROMMENT - Emilia Cornelia STOICA; Nicoleta Georgeta PANAIT (Challenges of the Knowledge Society)
Globally, the volume of public debt, most of which is sovereign debt, has increased significantly and although the macroeconomic development of most states has made good progress since the consequences of the global financial crisis triggered by the United States since 2007, their share has become a major concern for global financial equilibrium. In this context, the analysis of the evolution of public debt in each country as well as in the geographic areas of strategic importance for the international economic conjuncture is an imperative for international financial analysts and institutions as well as for those who develop forecasts and propose economic-financial policies in the short term, and especially in the medium and long term. The analysis of public debt in each country, region or community / association of sovereign states is of major importance both for assessing the financial stability and, implicitly, the economic at national, global as well as presently when capital, as well as goods and services circulate with great ease between countries and continents to identify potential risk factors that may affect the macroeconomic development and social life of the communities involved. The aggravation of free movement, along with the increase in public debt, along with other factors of an economic, political and social nature, contributes to the establishment of a new world economic order characterized by a new hierarchy of world states, new economic and financial relations between countries with a developed economy and those with important natural and human resources, but whose level of macroeconomic performance is well below the level of developed ones.